Pengaruh Store Image Dan Kualitas Pelayanan Terhadap Minat Beli Konsumen 212 Mart Cabang Panam Pekanbaru - Leni Silvia; Lie Othman; Syofiatul Safitri (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The purpose of this study was to determine the effect of Store Image and Service Quality on Consumer Purchase Interest at 212 Mart Panam Pekanbaru Branch. This study uses a quantitative analysis method. The sample in this study were consumers who shopped at 212 Mart Panam Pekanbaru Branch as many as 100 respondents. This study uses primary data and secondary data. Methods of data analysis using SPSS version 22. The results of the study show that store image has a positive and significant effect on consumer buying interest at 212 Mart Panam Pekanbaru Branch, service quality has a positive and significant effect on consumer buying interest at 212 Mart Panam Pekanbaru Branch and store image and service quality has a positive and significant effect on consumer buying interest at 212 Mart Panam Pekanbaru Branch.